The Reasonability of using artificial intelligence capabilities to ensure enterprise cybersecurity based on the concept of zero trust - Borodavka, V.V.; Yesin, V.I. (Radiotekhnika, 2025)
Modern enterprises face increasingly complex cybersecurity challenges, which require new approaches to digital asset protection. To ensure modern enterprise cybersecurity, a complex approach is needed, including adaptive and intelligent protection mechanisms that can withstand modern threats. The traditional perimeter-based protection model is not able to provide an adequate level of protection, as modern attacks are becoming increasingly sophisticated and enterprise infrastructure is undergoing significant changes due to the expansion of the attack surface, the use of cloud technologies and remote access. In this regard, an increasing number of organizations are focusing on the concept of zero trust, which is based on the principle of “never trust, always verify” and allows for secure access to their corporate resources anytime and anywhere, as well as their efficient functioning regardless of where they are located. Implementation of the zero-trust architecture involves the usage of modern methods and technologies, including artificial intelligence. The use of artificial intelligence technologies makes it possible to effectively detect threats, identify anomalies in systems and networks, automate access control, and dynamically monitor user behavior. This paper focuses on analyzing the role of artificial intelligence in ensuring cybersecurity of enterprises in the context of the zero-trust architecture. The paper aims to determine the possibilities of using artificial intelligence technologies to increase the level of protection of information systems and identify cyber threats within the framework of the zero trust architecture. The paper briefly describes the conceptual architecture of zero trust, its main logical components and approaches to integrating artificial intelligence into them. The analysis of existing approaches leads to the conclusion that the combination of artificial intelligence and the principles of zero trust contributes to the creation of a flexible and adaptive protection system capable of detecting, analyzing and neutralizing threats in real time, increasing resilience of an enterprise to cyber threats. In addition, the paper discusses the challenges associated with integrating artificial intelligence into the zero-trust architecture. In particular, it raises the issues of adapting outdated systems, creating mechanisms and recommendations for the gradual implementation of the zero-trust architecture and training staff to work effectively in the new environment, the need to standardize data and ensure consistency in security automation processes.